State dependent fiscal multipliers with preferences over safe assests - Ansgar Rannenberg (National Bank of Belgium, 2019)
I examine the effect of fiscal policy at the zero lower bound if households have preferences over safe assets (POSA) calibrated consistent with evidence on household savings behavior and individual discount rates, and empirical estimates of the effect of the supply of US government debt on government bond yields. POSA attenuate the effect of changes in the household's permanentincome on her consumption today and implies a wealth effect from government bonds. It therefore strongly increases the multiplier of a permanent expenditure change, moving it much closer to the multiplier of temporary expenditure changes. The result becomes even stronger with credit constrained households and firms.
Keywords: E52; E62; E32; 330; Fiscal multiplier of temporary and persistent expenditure changes; zero lower bound; wealth in the utility function